Posterior reversible encephalopathy syndrome in children: a case series - KUTLU, NURETTİN ONUR; Emeksiz, Serhat; Kutlu, NURETTİN ONUR; Caksen, Huseyin; Alkan, Gulsum; Yikmaz, Hulya Seker; Tokgoz, Huseyin (My University, 2016)
Posterior reversible encephalopathy syndrome is characterized by hypertension, seizure, headache, clouding of consciousness, and visual disturbance, and is diagnosed in the presence of typical lesions on magnetic resonance imaging. We retrospectively evaluated five patients who were diagnosed as having posterior reversible encephalopathy syndrome and followed up in Meram Medical Faculty, Pediatric Intensive Care and Hematology wards, between January 2010 and January 2014. We reviewed the demographic and clinical data, and neuroimaging findings. The primary diseases of the subjects included acute lymphocytic leukemia (n=2), Henoch-Scholein purpura (n=1), systemic lupus erythematous (n=1), and acute poststreptococcal glomerulonephritis (n=1). The mean age was 10 +/- 4.58 years (range, 5-14 years). Acute elevation of blood pressure was found in all patients (n=5). Initial neurologic manifestations included seizure, clouding of consciousness, headache, and visual disturbance. After the diagnosis was made through clinical evaluations and magnetic resonance imaging, complete clinical recovery was obtained in all patients with the appropriate therapeutic approach. In conclusion, posterior reversible encephalopathy syndrome should be considered in the differential diagnosis of patients who present with encephalopathy and underlying diseases such as nephritis, vasculitis, malignancy accompanied by hypertension, and a history of use of medication.